Exploring the Role of “Nasyiatul Aisyiyah” in Enhancing Women's Reading Literacy Skills - Adiningsih, Yulia; Damaianti, Vismaia S.; Mulyati, Yeti; Anshori, Dadang S.; Srinawati, Wawat (Journal of Language and Literature Studies, 2024)
Reading literacy has a very important role for women. Both in a personal context, as well as in the family and community environment. Reading skills allow women to access the information and knowledge needed to improve their self-competence. Women who have good reading skills can play a role in improving the quality of their children's education. This study aims to describe the role of Nasyiatul Aisyiyah in improving women's reading literacy skills and its impact on women's reading literacy skills in Bogor Regency. This research was conducted with members of Nasyiatul Aisyiyah in Bogor Regency. This study uses a descriptive qualitative method. Data was collected through interviews, observations, and documentation. The collected data is analyzed qualitatively through a comprehensive data identification and analysis process. To ensure the reliability of the data, the researcher used the triangulation method. The results of the study show that the structured reading literacy program initiated by Nasyiatul has successfully contributed to improving women's reading skills, especially Nasyiatul Aisyiyah members in Bogor Regency. This program not only provides benefits in literacy, but also supports the development of broader life skills, so that women become more prepared and empowered in facing challenges in society.